Evaluasi Kebijakan Pengembangan Kawasan Pertanian di Provinsi Papua Barat Melalui Analisis Iklim Oldeman dan Data Climate Hazards Group Infrared Precipitation with Stations - Arif Faisol; Bertha Ollin Paga; Risma Ulli Situngkir (Agritechnology, 2021)
Several areas in West Papua have been designated as National Agricultural Area Development, i.e. Manokwari, Sorong, Tambrauw, Teluk Wondama, Manokwari Selatan, Teluk Bintuni, Sorong Selatan, Kaimana, Fakfak, dan Raja Ampat. The priority commodities to be developed include rice, shallots, chilies, cocoa, palm oil, and nutmeg. Climate is one of the parameters that have a significant effect on growth and productivity, especially rain. This study aims to evaluate the policy of developing agricultural areas in West Papua through climate suitability analysis based on Oldeman climate zoning. Oldeman's climate zoning was analyzed using Climate Hazards Group Infrared Precipitation with Stations (CHIRPS) data recorded from 1981 to 2020. Research showed that the commodities and the area designated as Agricultural Area Development in West Papua are suitable with climatic conditions based on Oldeman climate zoning. However, the shallot is not suitable to be developed in West Papua Province.